6a + 1 chia hết cho 3a - 1
=> ( 6a - 2 ) + 3 chia hết cho 3a - 1
=> 2 ( 3a - 1 ) + 3 chia hết cho 3a - 1
mà 2 ( 3a - 1 ) chia hết cho 3a - 1
=> 3a - 1 thuộc Ư(3) = { -3 ; -1 ; 1 ; 3 }
Ta có :
3a - 1 | -3 | -1 | 1 | 3 |
3a | -2 | 0 | 2 | 4 |
a | loại | 0 | loại | loại |
6a+1 chia hết cho 3a-1
=>6a-2+3 chia hết cho 3a-1
=>2.(3a-1)+3 chia hết cho 3a-1
mà2.(3a-1) chia hết cho 3a-1
=>3 chia hết cho 3a-1
=> 3a-1thuộc Ư(3)={-3;-1;1;3}
=>3a={-2;0;2;4}
Vì 3a ko chia hết cho -2;2;4
=>a=0
6a+1 chia hết 3a-1
=> 2(3a-1)+3 chia hết cho 3a-1
=> 3 chia hết cho 3a-1
=> 3a-1 là Ư(3)={1;-1;3;-3}
Vì 3a-1 chia 3 dư 2 hoặc -1
=> 3a-1=-1
=> a=0